Kinotherapy practice with people hospitalized in psychosocial care unit: experience report - Siqueira, Daiana Foggiato de (2020)
Objective: To report the experience of a group that promotes the practice of kinotherapy with people admitted to a Psychosocial Care Unit. Methodology: This is an experience report lived by the extension project team “Humanizing Practices of Mental Health Care” of the “Mental Health Care and Health Training Research Group” at the Federal University of Santa Maria. The kinotherapy was performed with users who are hospitalized in a Psychosocial Care Unit of a University Hospital in the State of Rio Grande do Sul. The practices lasted around 60 minutes, being performed in the hospital's courtyard once a week with average participation. of 20 people. Results: Cinoterapia has the purpose of helping social, educational and therapeutic interactions based on the contact and socialization of the participant with the dog. Through the mediation of health professionals, participants are encouraged as to their personal skills and abilities, as well as the promotion of self-care, being a practice recognized by the team that accompanies users. Conclusion: It is understood that the process of humanizing mental health care is necessary and should be disseminated through studies, since kinotherapy favors, in addition to new interpersonal and affective relationships with other people in the environment, a clinical improvement symptoms manifested by users.